Analysis of the Ability of Class IX Students In Solving Quadratic Equation Problems - Kuswoyo, Ali (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
The problem addressed in this study is the variation in the ability of ninth-grade students at SMPN Satu Atap 1 Kalipucang in solving mathematical problems, particularly quadratic equations. Some students demonstrate excellent abilities, while others face difficulties in understanding and solving quadratic equation problems accurately and systematically. This variation in abilities highlights challenges in mathematics education that need to be addressed. This study aims to evaluate students' ability to solve mathematical problems, with a focus on quadratic equations. The method used is descriptive analysis with a combination of quantitative and qualitative approaches. The quantitative technique is used to assess students' ability levels through tests, while the qualitative technique is employed to delve deeper into the students' thought processes through interviews. The results indicate that students with high and very high abilities can solve quadratic equation problems well. On the other hand, students with medium ability levels struggle with understanding basic concepts and structured problem-solving steps. Meanwhile, students with low and very low abilities have difficulty understanding the material in-depth, resulting in their inability to solve the problems effectively. These findings suggest the need for a more systematic teaching approach, focusing on strengthening basic understanding and providing additional practice to enhance problem-solving skills, particularly in quadratic equations.Analisis Kemampuan Peserta Didik Kelas IX Dalam Menyelesaikan Masalah Persamaan Kuadrat ABSTRAKPermasalahan yang dihadapi dalam penelitian ini adalah adanya variasi kemampuan peserta didik kelas IX di SMPN Satu Atap 1 Kalipucang dalam memecahkan masalah matematika, khususnya materi persamaan kuadrat. Beberapa peserta didik menunjukkan kemampuan yang sangat baik, sementara yang lain mengalami kesulitan dalam memahami dan menyelesaikan soal-soal persamaan kuadrat secara tepat dan sistematis. Variasi kemampuan ini menunjukkan adanya tantangan dalam pembelajaran matematika yang perlu diatasi. Penelitian ini bertujuan untuk mengevaluasi kemampuan peserta didik dalam memecahkan masalah matematika, dengan fokus pada topik persamaan kuadrat. Metode yang digunakan adalah analisis deskriptif dengan pendekatan kuantitatif dan kualitatif. Teknik kuantitatif digunakan untuk mengukur tingkat kemampuan peserta didik melalui tes, sementara teknik kualitatif digunakan untuk menggali lebih dalam proses berpikir peserta didik melalui wawancara. Hasil penelitian menunjukkan bahwa peserta didik dengan kemampuan tinggi dan sangat tinggi mampu menyelesaikan soal-soal persamaan kuadrat dengan baik. Sebaliknya, peserta didik dengan kemampuan sedang mengalami kesulitan dalam memahami konsep dasar dan langkah-langkah penyelesaian. Sementara itu, peserta didik dengan kemampuan rendah dan sangat rendah kesulitan dalam memahami materi secara mendalam, sehingga tidak dapat menyelesaikan soal dengan baik. Temuan ini mengindikasikan perlunya pendekatan pembelajaran yang lebih sistematis, dengan fokus pada penguatan pemahaman dasar dan latihan ekstra untuk meningkatkan keterampilan pemecahan masalah matematika, khususnya pada materi persamaan kuadrat.Kata Kunci :Analisis; Persamaan Kuadrat; Variasi kemampuan